2018
DOI: 10.1111/pce.13323
|View full text |Cite
|
Sign up to set email alerts
|

Terpenes associated with resistance against the gall wasp, Leptocybe invasa, in Eucalyptus grandis

Abstract: Leptocybe invasa is an insect pest causing gall formation on oviposited shoot tips and leaves of Eucalyptus trees leading to leaf deformation, stunting, and death in severe cases. We previously observed different constitutive and induced terpenes, plant specialized metabolites that may act as attractants or repellents to insects, in a resistant and susceptible clone of Eucalyptus challenged with L. invasa. We tested the hypothesis that specific terpenes are associated with pest resistance in a Eucalyptus grand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…r 2 of cross-validation for α-pinene = 0.24, concentration range ca. 0–15 mg g −1 ) 18 . These studies suggest it should be possible to improve the precision of the existing calibrations by adding samples with a wider range of terpene concentration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…r 2 of cross-validation for α-pinene = 0.24, concentration range ca. 0–15 mg g −1 ) 18 . These studies suggest it should be possible to improve the precision of the existing calibrations by adding samples with a wider range of terpene concentration.…”
Section: Resultsmentioning
confidence: 99%
“…100 g of dried, ground plant sample), 13 a luxury not always available in experimental studies. A few studies correlated the spectra of dried leaves to oil-based laboratory analyses with success, notably with aromatic herbs 13,17 and Eucalyptus trees, 18 and this procedure has yet to be tested for conifer trees (but see Ercioglu et al. 13 for coniferous shrubs).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the extent of damage caused by these larvae is commensurate to the upregulation of the biosynthesis of the VOC blend [ 75 , 76 ]. Iso-pinocarveol is proposed to potentially act as a recruiter of parasitoids in addition to having toxic properties [ 86 ] ( Table 2 ).…”
Section: Terpenoids In Plant–insect Interactionsmentioning
confidence: 99%
“…This strategy could be particularly useful or practical in mitigating and managing the agricultural and economic impacts of these unwanted insect pests. A study [ 86 ] has demonstrated an important association between increased γ-terpinene and α-pinene production in Eucalyptus grandis and its subsequent susceptibility to pest infestation, indicating the potential utility of these terpenes as attractants to E. grandis pest Leptocybe invasa , or a potential decoy/trap when expressed in non-host plant species.…”
Section: Terpenoids In Plant–insect Interactionsmentioning
confidence: 99%
“…Metabolomics in forest tree-biotic stress interactions have been limited to the study of specific secondary metabolites, e.g. terpenes (Oates et al., 2015; Naidoo et al., 2018), using methods such gas or liquid chromatography coupled to mass spectrometry (GC-MS and LC-MS, respectively) and near-infrared reflectance (NIR) technologies. Metabolomics in European common ash, Fraxinus excelsior , revealed different profiles associated with resistance and tolerance to the fungus, Hymenoscyphus fraxineus (Sambles et al., 2017).…”
Section: Introductionmentioning
confidence: 99%